George Caleb Bingham Missouri's famed painter and forgotten politician - Nagel, Paul C. (Missouri heritage readers., 2005)
"Paul Nagel's biography of nineteenth-century American painter and statesman George Caleb Bingham assesses Bingham's artistic achievements and his service as a political leader in Missouri during Reconstruction. Illustrations include both well-known and rarely seen works by Bingham"--Provided by publisher.